2010
DOI: 10.4028/www.scientific.net/kem.455.495
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Microhardness of Nickel Electroformed under Vacuum-Degassing Conditions

Abstract: Ni deposits were prepared from a nickel sulfamate type electrolyte bath under vacuum-degassing and temperature-gradient conditions without any additives. Morphology and microhardness of the deposits obtained at the current density of 1A/dm2, 3A/dm2, 5A/dm2 and 7A/dm2 were examined and analyzed. Experimental results showed that the deposits obtained under vacuum-degassing and temperature-gradient conditions exhibited fewer pinhole defects and finer grain size comparing with those formed under conventional depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Recently, many investigations have been made on electroforming. Ming et al (2011) investigated the feasibility of a new micro-electroforming technique. A series of experiments were performed using special equipment, developed by the authors, followed by the evaluating the surface morphology of nickel microelectroforms using a scanning electron microscope (SEM).…”
Section: Nickel Electroformingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many investigations have been made on electroforming. Ming et al (2011) investigated the feasibility of a new micro-electroforming technique. A series of experiments were performed using special equipment, developed by the authors, followed by the evaluating the surface morphology of nickel microelectroforms using a scanning electron microscope (SEM).…”
Section: Nickel Electroformingmentioning
confidence: 99%
“…Further, the bipolar RS phenomenon can be explained by the voltage-polarity-dependent movement of oxygen ions near the interface. Ming et al (2011) prepared Ni deposits from a nickel sulfamate type electrolyte bath under vacuum-degassing and temperature-gradient conditions without any additives. Morphology and micro-hardness of the deposits obtained at the current density of 1, 3, 5 and 7A/dm 2 were examined and analyzed.…”
Section: Nickel Electroformingmentioning
confidence: 99%
“…Therefore, our research group developed an unconventional electroforming process, electrolyte vacuum boiling electroforming, by introducing vacuum degassing technology [3,4] and surface boiling [5] technology into the electrodeposition process [6]. Our studies have shown that the electrolyte vacuum boiling electroforming process can generate the components with markedly improved surface quality (almost no pinholes and nodule) and desirable microstructures with fine grains and good compactness [7][8][9][10][11]. To explore the mechanisms determining the favorable effects, this paper focuses on analyzing cathodic potential and interelectrode resistance of the electrolyte vacuum boiling electroforming process carried out under different reduced pressure and cathode temperature.…”
Section: Introductionmentioning
confidence: 99%